ضمانات الاستثمار الأجنبي في التشريع الجزائري - مبروك, عبد النور (جامعة مسيلة, 2018)
Foreign investment is one of the essential elements of economic development, especially for developing countries that do not have the domestic resources to finance their economic activities. As a result, host countries are investing in creating a favorable climate for foreign investors by providing incentives to encourage them to invest in their country and provide them with legal protection. For several years, Algeria has worked tirelessly to improve the investment climate by creating the conditions to attract foreign investment by developing the appropriate economic framework and the clear legal framework. The interest for the economy depends on the importance of the guarantees granted to the investors and, on this basis, the Algerian legislator, since the publication of the legislative decree n ° 93-12 of October 5th, 1993 relating to the promotion of the investment , seeks to provide as many legal and judicial guarantees to foreign investors Algeria has become one of the few developing countries with advanced legislation to provide adequate protection for foreign investors. With regard to legal guarantees, Algeria has modified the investment legislation in line with the changing global economic situation. By adopting the guarantees and principles of international law investments: equal treatment. the transfer of capital and the maintenance of legislation ... With regard to judicial guarantees, the Algerian legislator has removed any ambiguity on the question of the settlement of disputes relating to foreign investments, leaving the foreign investor the freedom to choose the appropriate means to settle the dispute between the Algerian State and the foreign investor by dedicating International arbitration through the amendments to the laws relating to foreign investments, and by adopting a new code of civil procedures. In order to improve its international investment climate and reassure foreign capital, Algeria has ratified a number of international multilateral investment treaties and has concluded several bilateral international agreements, all of which provide for the possibility of international arbitration. to rule on investment disputes. These legal and judicial guarantees - in addition to the many incentives and benefits - and the good faith shown by Algeria in its adherence to several international investment treaties, provide adequate protection for foreign investors against all non-commercial risks and facilitate and attract foreign investment to our country
Keywords: Investment. Guarantees. Maintenance of Legislation. Arbitration. Equal Treatment. Transfer of Capital. Expropriation